Contingency planning for famines and other acute food shortages: a brief review. - Sarma, J. S. (International Food Policy Research Institute, 1983)
Although international and national initiatives related to food security are receiving attention, other issues, such as contingency planning for famines and other acute food shortages are also important. The adverse effects of these shortages are particularly severe in low-income developing countries and among poorer groups in those countries. Many people have died of famine not because of food production shortages, but because there were serious problems with the food distribution systems, or because vulnerable groups had inadequate purchasing power. Not enough is known about the measures needed to deal with such emergencies in different countries with differing food systems. Actions to mitigate the hardships arising from the scarcities of work, water, and food associated with severe droughts will vary.JV These include improving the exchange entitlements of the people;^/ adopting crop life-saving techniques, introducing alternative crop strategies, and undertaking compensatory cropping programs in irrigated areas; providing drinking water; and preventing and recouping animal losses.